2023
DOI: 10.3390/jcm12041460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individualised High Positive End-Expiratory Pressure and Crystalloid Administration on Postoperative Pulmonary Function in Patients Undergoing Robotic-Assisted Radical Prostatectomy: A Prospective Randomised Single-Blinded Pilot Study

Abstract: Objectives: Robotic-assisted laparoscopic prostatectomy (RALP) is typically conducted in steep Trendelenburg position (STP). The aim of the study was to evaluate whether crystalloid administration and individual management of positive end-expiratory pressure (PEEP) improve peri- and post-operative pulmonary function in patients undergoing RALP. Design: Prospective randomised single-centre single-blinded explorative study. Setting: Patients were either allocated to a standard PEEP (5 cmH2O) group or an individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…When PEEP was individualized, resulting in levels between 12-14 cmH 2 O, arterial oxygenation and respiratory system compliance were higher compared to a lower fixed level (i.e. 5 cmH 2 O) [22,31,33,34]. However, in the same position, increasing PEEP to 10 cmH 2 O raised total mechanical power compared to 5 cmH 2 O of PEEP, although respiratory system elastance did not change.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When PEEP was individualized, resulting in levels between 12-14 cmH 2 O, arterial oxygenation and respiratory system compliance were higher compared to a lower fixed level (i.e. 5 cmH 2 O) [22,31,33,34]. However, in the same position, increasing PEEP to 10 cmH 2 O raised total mechanical power compared to 5 cmH 2 O of PEEP, although respiratory system elastance did not change.…”
Section: Discussionmentioning
confidence: 93%
“…During mechanical ventilation, PEEP levels usually do not exceed 5 cmH 2 O, which can be not sufficient to avoid lung atelectasis and prevent VILI [22]. Previous studies suggested to select PEEP achieving the maximal respiratory system compliance, the lower driving pressure or according to the intrabdominal pressure [9,22,[30][31][32]. When PEEP was individualized, resulting in levels between 12-14 cmH 2 O, arterial oxygenation and respiratory system compliance were higher compared to a lower fixed level (i.e.…”
Section: Discussionmentioning
confidence: 99%